Crowd sourcing energy poverty data in South African informal settlements: the opportunity of mobile phone technology - Pillay, Kimenthrie (Energy Research Centre, 2017)
Energy poverty undermines development at a large scale. It is most overtly experienced in informal settlements, where the use of fuels like paraffin, charcoal and wood prove hazardous and harmful to health and wellbeing. The expenditure on and use of energy services in informal settlements are largely undefined, which severely undermines the success of energy access and safety initiatives. Despite the poverty of informal settlements, mobile phone ownership is high in these areas. This research aims to explore the potential and applicability of a digital data collecting systems using a mobile application that is accessible on entry-level mobile phones with basic internet access to collect information about energy access, affordability and multiple fuel use in these areas. As part of this research, a mobile application platform and data collection platform was developed which enables survey design and data collection in real time. The platform allows for creation of weekly surveys that question energy use, expenditure and affordability; it also offers other functions that are designed to increase awareness of fuel safety and efficiency. The application was piloted in lmizamo Yethu in Cape Town. Six weeks of continuous data was extracted from 200 users using airtime incentives with an overall reach of 306 households. The quality and quantity of data received was of high calibre. The results indicate that the potential for using this system and mobile phones as a data-collecting tool in Africa is high.